Response of chickpea (Cicer aritienum L.) to sulphur and zinc nutrients application and rhizobium inoculation in north western Ethiopia - Shewangizaw, B. (Haramaya University, 2017)
In sub-Saharan Africa, plant nutrient deficiency, due to nutrient mining, is a major growth limiting factor for crop production. As a result, some soils become non responsive to Rhizobial inoculation. In an effort to find out possible correction, a field experiment was carried out on-farm, during 2016/17 growing season, at Gondar Zuria woreda in Tsion and Denzaz Kebeles to evaluate the effect of Rhizobium inoculation, S and Zn application on yield and yield parameters, nodulation, N and P uptake on chickpea. The soil at the experimental sites were previously diagnosed as non responsive to Rhizobium inoculation and P fertilizer application on chickpea (Cicer aritienum L.) and had low OM, N, P, S and Zn. The experiment included twelve treatments developed via factorial combination of two level of inoculation (Rhizobium inoculated, un-inoculated), three level of S (0, 15, 30 kg Sulphur ha-1) and two levels of Zn (0, 1.5 kg Zinc ha-1). The treatment was laid out in randomized complete block design with three replications. All plots have received basal application of 20 kg N ha-1and 20 kg P ha-1 uniformly. Zinc in the form of ZnSO4 was applied through foliar application and the remaining nutrients were applied at planting directly to the soil. Mean separation was made using the least significant difference (LSD) test at 5% level of probability. Analysis of variance showed that except plant height at both location and shoot dry weight and number of seed per pod at Tsion, all the remaining growth parameters (root length and root dry weight), yield and yield related traits (number of primary branches, number of pod, number of seed, hundred seed weight, grain and straw yield), crop phenology (days to 50% flowering and days to physiological maturity), nodulation scores (nodule number, nodule volume, nodule dry weight, effective nodule and nodulation rating), N and P uptake at both locations were significantly affected by the treatments. The highest (1775.5 kg ha-1) mean value of seed yield over locations was obtained from combined application of Rhizobium and 30 kg S ha-1 which resulted in 28 % (389 kg ha-1) increase over the control. The result also indicated that P use efficiency of chickpea was improved with Rhizobium inoculation and S fertilizer application. The partial budget analysis also showed that the maximum (ETB 37069 ha-1) and minimum (ETB 30050 ha-1) net benefit were obtained from combined application of Rhzobium inoculation and 30 kg S ha-1and from the control check, respectively. The result determined a net benefit penalty of 23.4% (ETB 7019 ha-1). Hence, Rhizobium inoculation with application of 30 kg S ha-1 could be recommended for chickpea production at the experimental locations in Gonder Zuria Woreda.